Konstruksi Identitas Diri melalui Genealogi: Studi Etnoparenting tentang Pencegahan “Kepaten Obor” dalam Tradisi Riyoyoan Masyarakat Jawa - Nadila Putri Andini; Suharti Suharti; Mallevi Agustin Ningrum; Dhian Gowinda Luh Safitri; Kartika Rinakit Adhe; Budi Purwoko (Pendidikan Guru PAUD Universitas Persatuan Guru Republik Indonesia Semarang, 2026)
This study explores ethnoparenting strategies used by parents to introduce family genealogy to young children during Riyoyoan (Eid al-Fitr) in Mojokerto. Using a qualitative approach with a narrative inquiry design, data were collected through in-depth interviews, passive participant observation, and reflective journals involving six participants. The findings indicate that introducing family genealogy is an effort to prevent “kepaten obor,” a Javanese concept referring to the loss of ancestral continuity and intergenerational kinship ties. The strategies included using the grandmother’s house as a shared memory center (place attachment), teaching kinship terms such as Pakdhe and Budhe to foster social etiquette, limiting gadget use to strengthen face-to-face interaction, and using visual media, such as old photographs, alongside grave visitation rituals. This study contributes to understanding traditional holidays as natural learning environments for strengthening children’s interpersonal intelligence, sense of belonging, and mental resilience. For early childhood educators, the findings provide a conceptual reference for integrating ancestral values into local wisdom-based curricula through programs such as “Genealogy Day.”